The Impact of Turkish domestic social-political factors on Turkish-US relations: Feeding conspiracy and anti-Americanism - Hovsepyan, Levon (YSU Journal of International Affairs, 2022)
Besides international structural factors, Turkish domestic level variables and socio-political processes are also essential for Turkish foreign policy transformation. The article considers current unprecedented crisis in Turkish-US relations in the context of Turkish social-political processes. In the general trend of securitization of Turkish foreign policy anti-Westernism and anti-Americanism in Turkey are in progress, which is the outcome of discursive hegemony of the ruling AKP. On the one hand, anti-Americanism and the demonization of USA’s image gives Erdogan a useful tool in conservative, nationalist support mobilization in the country. On the other hand, he tries to impose Turkey’s image in the international realm as an assertive power of resistance against the Western hegemony in the Islamic world․
Keywords: Turkish-American relations; Justice and development party; Erdogan; military coup attempt; anti-Americanism